e ^ { y } ( e ^ { x } + 1 ) d y = e ^ { x } ( 1 - e ^ { y } ) d x
Solve for d (complex solution)
\left\{\begin{matrix}\\d=0\text{, }&\text{unconditionally}\\d\in \mathrm{C}\text{, }&ye^{y}\left(e^{x}+1\right)-xe^{x}\left(1-e^{y}\right)=0\end{matrix}\right.
Solve for d
\left\{\begin{matrix}\\d=0\text{, }&\text{unconditionally}\\d\in \mathrm{R}\text{, }&ye^{y}\left(e^{x}+1\right)-xe^{x}\left(1-e^{y}\right)=0\end{matrix}\right.
Share
Copied to clipboard
\left(e^{y}e^{x}+e^{y}\right)dy=e^{x}\left(1-e^{y}\right)dx
Use the distributive property to multiply e^{y} by e^{x}+1.
\left(e^{y}e^{x}d+e^{y}d\right)y=e^{x}\left(1-e^{y}\right)dx
Use the distributive property to multiply e^{y}e^{x}+e^{y} by d.
e^{y}e^{x}dy+e^{y}dy=e^{x}\left(1-e^{y}\right)dx
Use the distributive property to multiply e^{y}e^{x}d+e^{y}d by y.
e^{y}e^{x}dy+e^{y}dy-e^{x}\left(1-e^{y}\right)dx=0
Subtract e^{x}\left(1-e^{y}\right)dx from both sides.
e^{y}e^{x}dy+e^{y}dy+\left(-e^{x}+e^{y+x}\right)dx=0
Use the distributive property to multiply -e^{x} by 1-e^{y}.
e^{y}e^{x}dy+e^{y}dy+\left(-e^{x}d+e^{y+x}d\right)x=0
Use the distributive property to multiply -e^{x}+e^{y+x} by d.
e^{y}e^{x}dy+e^{y}dy-e^{x}dx+e^{y+x}dx=0
Use the distributive property to multiply -e^{x}d+e^{y+x}d by x.
\left(e^{y}e^{x}y+e^{y}y-e^{x}x+e^{y+x}x\right)d=0
Combine all terms containing d.
\left(xe^{x+y}-xe^{x}+ye^{x+y}+ye^{y}\right)d=0
The equation is in standard form.
d=0
Divide 0 by e^{y+x}y+e^{y}y-e^{x}x+e^{y+x}x.
\left(e^{y}e^{x}+e^{y}\right)dy=e^{x}\left(1-e^{y}\right)dx
Use the distributive property to multiply e^{y} by e^{x}+1.
\left(e^{y}e^{x}d+e^{y}d\right)y=e^{x}\left(1-e^{y}\right)dx
Use the distributive property to multiply e^{y}e^{x}+e^{y} by d.
e^{y}e^{x}dy+e^{y}dy=e^{x}\left(1-e^{y}\right)dx
Use the distributive property to multiply e^{y}e^{x}d+e^{y}d by y.
e^{y}e^{x}dy+e^{y}dy-e^{x}\left(1-e^{y}\right)dx=0
Subtract e^{x}\left(1-e^{y}\right)dx from both sides.
e^{y}e^{x}dy+e^{y}dy+\left(-e^{x}+e^{y+x}\right)dx=0
Use the distributive property to multiply -e^{x} by 1-e^{y}.
e^{y}e^{x}dy+e^{y}dy+\left(-e^{x}d+e^{y+x}d\right)x=0
Use the distributive property to multiply -e^{x}+e^{y+x} by d.
e^{y}e^{x}dy+e^{y}dy-e^{x}dx+e^{y+x}dx=0
Use the distributive property to multiply -e^{x}d+e^{y+x}d by x.
\left(e^{y}e^{x}y+e^{y}y-e^{x}x+e^{y+x}x\right)d=0
Combine all terms containing d.
\left(xe^{x+y}-xe^{x}+ye^{x+y}+ye^{y}\right)d=0
The equation is in standard form.
d=0
Divide 0 by e^{y+x}y+e^{y}y-e^{x}x+e^{y+x}x.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}